KOMPOSISI TERIPANG (HOLOTHUROIDEA) DI PANTAI SAIBI KECAMTAN SIBERUT TENGAH MENTAWAI SUMATERA BARAT - Juliarti, Reni; Widiana, Rina; Meriko, Lince (STKIP PGRI Sumbar, 2013)
ABSTRACT Sea cucumbers (Holothuroidea) is one class of Echinodermata (thorn-skinned animals) that live in coastal waters Saibi that have no nutritional value and high economic. This causes the animal much overexploited by communities around the coast that have reduced the presence of population. Based on this research has been done on the composition of the cucumbers were found in Saibi Beach Middle Siberut Mentawai District, in December 2012. This research is descriptive and sampling using belt transect method with squares measuring 1 m2. Sample identification is done in Laboratory Animal Ecology, State University of Andalas Padang. The results showed that sea cucumbers were found to be composed of 6 species which consists of 1 class, 1 order, 2 Family and 4 genus Holothuria consisting ie 3 species, whereas Stichopus, Bohadchia Thelenota and 1 species each. Highest density at Station I (3.66 indivedu/m2) and the lowest at Station III (2.99 individu/m2). Highest frequency contained in the Station I (3.66%) and the lowest at the third station (2.99%). Indeks Divesty is highest at the first station (1.4672) and lowest in the Station II (1.3693). Spearman correlation level obtained at the third station r count is smaller than α r table at 5% level (0.829) correlated not real, physical and chemical factors in the Pantai Saibi Kecamatan Siberut Tengah Mentawai District, temperature range 27-300 C, pH 74-75, DO 7,1-8,4 ppm and salinity 15.18-50.20 mg / L